Managerial responses to incentives: Control of firm risk, derivative pricing implications, and outside wealth management - Jens Carsten Jackwerth; James E. Hodder (University of Konstanz, Center of Finance and Econometrics (CoFE), 2008)
We model a firm's value process controlled by a manager maximizing expected utility from restricted shares and employee stock options. The manager also dynamically controls allocation of his outside wealth. We explore interactions between those controls as he partially hedges his exposure to firm risk. Conditioning on his optimal behavior, control of firm risk increases the expected time to exercise for his employee stock options. It also reduces the percentage gap between his certainty equivalent and the firm's fair value for his compensation, but that gap remains substantial. Managerial control also causes traded options to exhibit an implied volatility smile.
urn:nbn:de:bsz:352-opus-54367
Keywords: 330